Pengadaan Fasilitas untuk Penyandang Disabilitas di Ambarrukmo Plaza Yogyakarta Sesuai dengan Peraturan Perundang-Undangan - Rizki Sandi Laksono; Ane Permatasari (Pencerah, 2021)
The existence of Yogyakarta Special Region Regulation No. 4 of 2012 on Protection and Fulfillment of The Rights of Persons with Disabilities shows that the DIY Regional Government strives to fulfill the rights of persons with disabilities. In DIY Regional Regulation No. 4 of 2012 on Protection and Fulfillment of The Rights of Persons with Disabilities regulates accessibility in the use of public facilities for persons with disabilities. Research is conducted using qualitative descriptive research methods and data obtained from interview results, documentation, and observations. Based on research conducted by the authors, DIY Regional Regulation No. 4 of 2012 on the Protection and Fulfillment of The Rights of Persons with Disabilities has not been effective because there are no sanctions for violators of the rights of persons with disabilities in the accessibility of the use of public facilities in DIY Regional Regulation No. 4 of 2012 on the Protection and Fulfillment of The Rights of Persons with Disabilities. Meanwhile, in Ambarrukmo Plaza as one of the malls located in Yogyakarta Special Region has provided facilities and companion for people with disabilities, such as wheelchairs, elevators, toilets, and parking spaces. Although facilities for people with disabilities are already available at Ambarrukmo Plaza, they do not meet the criteria set. People with disabilities with visual impairment and deafness must also be accompanied, due to the lack of facilities such as signage and information speakers.